Restoring Quality of Life: Assessing the Impact of Free Flap Reconstruction in Coronavirus Disease 2019-Associated Rhino-Orbital Mucormycosis Patients - Rao, Neeraj; Agrawal, Anand; Kapoor, Akshay; Mago, Vishal; Vathulya, Madhubari; Chattopadhyay, Debarati (Indian Journal of Plastic Surgery, 2023)
Background In India, between May 5 and July 2021, 41,512 cases and 3,554 deaths due to mucormycosis were reported in coronavirus disease 2019 (COVID-19)-infected patients or COVID-19-recovered patients. COVID-19-associated rhino-orbital mucormycosis (CAROM) has been associated with adverse effects that can affect oral health, vision, and physical as well as emotional functioning. After the radical debridement of CAROM and antifungal therapy, reconstructive surgery should be employed to restore function and aesthetics; however, limited clinical data exist on its potential effect on the quality of life (QOL) of these patients.Objective Our objective was to assess the QOL among CAROM patients reconstructed with free flap surgery.Materials and Methods This analysis studied 19 patients of CAROM who had maxillectomy and/or orbital exenteration defects reconstructed with free flaps at a tertiary care center. All these patients were free from any residual disease, as confirmed by tissue biopsy taken from the affected area. The QoL of these patients was assessed 1 week preoperatively and 4 to 6 months postoperatively using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module (EORTC QLQ-HN43) questionnaire module.Results There was a statistically significant improvement in 10 out of the total 19 parameters (p < 0.05) which include pain in the mouth, problems opening mouth, speech, swallowing, weight loss, dry mouth and sticky saliva, body image, fear of progression, social contact, and social eating.Conclusion The EORTC QLQ-HN43 questionnaire module presented a statistically significant improvement in the functional as well as psychological status of the CAROM patients undergoing reconstruction by free flap surgery.
Keywords: COVID-19; free flap; quality of life; mucormycosis; body image; aesthetics